Catch a Wolf - Rose, A. Katie (Los Gatos Smashwords Edition, 2015)
Raine, Ly'Tana and the others escape Brutal's trap, but with dire consequences. Kel'Ratan has been grievously injured, and Rygel must take him to safety to save his life. Yet, they are not out of danger. A monstrous storm called the Wrath of Usa'a'mah has halted their flight from Khalid and they must seek shelter within a remote monastery or die under the storm's power.But High King Brutal has allied himself with the deadly assassins, the Shekinah Tongu. The secretive clan has sworn out a Blood Oath against Rygel in retaliation for his leaving their brothers in the forest to die. With their hellish hounds and Brutal's dark wizard, Ja'Teel, they track Raine and Ly'Tana through the devastation left by the storm. Raine leads them into the west, toward Ly'Tana's home of Kel'Halla, with Brutal's menace confronting them at every turn.As he finds himself falling in love with the exotic Ly'Tana, Raine is plagued by a mysterious voice in his head. Is he going crazy? In Raine, Ly'Tana discovers the one man she cannot live without. However, an evil entity has targeted Ly'Tana, bent on her destruction. How can Raine, Rygel, Kel'Ratan and her griffin bodyguard, Bar, keep her safe from its vast, unseen power?Hunted by Brutal and his evil allies, Raine, Ly'Tana and their friends discover a new, and very strange, force dogging their trail - a pack of enormous, cunning wolves. Mysterious wolves who call to Raine in the night, and bring alive the secret he's kept hidden, even from himself. Taunted by nightmarish visions, Raine is forced to confront his own dark demon - the beast within himself.Who will catch Raine and Ly'Tana first? Brutal and his pets - or the wolves?Thus begins the second novel of the Saga of the Black Wolf series.
105547